Experimental analysis on shredder for recycling thermoplastics using injection moulder. (2022) - Muthiah, Essakkiappan; Rathanasamy, Rajasekar; Ravichandran, Dharmaprakash; Palanichamy, Dhayananth; Sivaraj, Santhosh
Abstract: The current work mainly focused on analyzing the performance of plastic crushers designed and fabricated as an alternative to traditional impact crushers. The operating mechanism of the injection molding machine combined with the shredder consists of two phases: cutting the plastic using a double-edged blade, then loading the shredded plastic into the hopper and pressing it against the desired mold. For a safer design, the blades were designed based on PET materials as they have higher tensile strength (61.61 MPa) compared to other plastic materials. The time required to shred the plastic was directly proportional to the thickness of the plastic material and the type of plastic material used. For polyethylene terephthalate (PET) with thicknesses of 0.25 mm and 1.5 mm, the cutting time required for the shredder was found to be 11 s and 21 s, respectively. The calculated shear force and shaft torque per blade appeared to be 7.22 N and 108.3 Nm, respectively. It was observed that the torque required to cut the plastic with this shredder was lower than that of the impact crusher. As a result, the overall mechanical complexity and cost of grinding are reduced.